Rhinoplasty as an Adjunct to Facial Rejuvenation - Hamilton, Grant S. (Facial Plastic Surgery, 2021)
Rhinoplasty typically is not considered a part of the repertoire facial rejuvenation surgery but the same involutional changes that affect the other structures of the face also impact the nose and midface. Comparatively little has been written about nasal rejuvenation. Rhinoplasty may be an under-recognized but a useful adjunct to the rejuvenation of the aging face. The aging nose presents unique pathology due to the involutional changes that affect the cartilage and supporting structures. A comprehensive facial rejuvenation plan should address these progressive effects.
Keywords: rhinoplasty; aging; nose; rejuvenation